Incidence of saw fly, Athalia lugens proxima Klug. as influenced by level of irrigation and fertilizers on mustard (The Journal of Plant Protection Sciences, 2020)
The experiments were conducted in the Instructional farm of Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal in two successive Rabi seasons of 2005-06 and 2006-07with an objective to study the incidence of saw fly (Athalia lugens proxima Klug.) as influenced by level of irrigation and fertilizers on mustard c.v. NC-1 (Jhumka) of Brassica campestris var. yellow sarson. Highest saw fly population (0.26 larvae/plant) was recorded on the crop grown without irrigation and medium level of fertilizers (60:30:30 Kg NPK ha-1) while lowest population level (0.10 larvae/plant) was observed at highest level of irrigation (three) coupled with medium level of fertilizers (60:30:30 kg NPK ha-1) and two irrigations coupled with lowest level of fertilizers (40:20:20 Kg NPK ha-1).
Keywords: Mustard saw fly; irrigation; fertilizers